Development of Maritime Research in the Digital Era Bibliometric Analysis - Yusup, Muhammad Firdaus Bin; Syaifullah, Muhammad (Maritime Park: Journal of Maritime Technology and Society, 2025)
This study aims to analyze the development of maritime research in the digital era through a bibliometric approach, with a particular focus on scientific publications in the period 2015-2024. The methodology used includes data collection from two major academic databases, namely Scopus and Web of Science, selected for their comprehensive coverage and availability of metadata. The data collection process included the use of a systematic search string with keywords such as "maritime research", "digital transformation", and "smart maritime". The analysis was carried out using VOSviewer software that allows for network visualization and analysis. The findings from the analysis indicate a significant increase in the volume of publications related to digital maritime, reflecting the acceleration of research driven by technologies such as the Internet of Things (IoT) and artificial intelligence. The findings also identify maritime ports as the epicenter of digital transformation, with a dominant research focus on the digitalization of port operations and cybersecurity. Despite the progress, there is a significant research gap regarding the socio-technical aspects of digital transformation, including its impact on the workforce and coastal communities. Thus, the results of this study not only provide a deep understanding of maritime research trends, but also serve as an important reference for researchers, industry practitioners, and policy makers to formulate strategies and policies that support innovation and the application of digital technology in the maritime sector. This study is expected to help anticipate challenges that may arise along with the continued development of digital transformation.era and becomes a reference for the development of maritime research policies and strategies in the future.